Neural Substrates of Word Generation during Stroke Recovery: The Influence of Cortical Hypoperfusion - V. Prabhakaran; S. P. Raman; M. R. Grunwald; A. Mahadevia; N. Hussain; H. Lu; P. C. M. Van zijl; A. E. Hillis (Behavioural Neurology)
Several studies have demonstrated reorganization of cognitive and motor function caused by stroke. This study examined the influence of hypoperfused brain regions, in addition to the area of the infarct itself, on reorganization of the cognitive processes underlying word generation in stroke patients. In addition, we also sought to determine the influence of hypoperfusion on the blood oxygen level dependent/(BOLD) effect. Subjects with left and right subacute or chronic subcortical strokes, along with normal controls, were imaged while performing a verbal fluency task (word generation). The study population included six normal subject and six stroke patients with subcortical infarcts and cortical hypoperfusion in the middle cerebral artery territory who had recovered or improved markedly in word fluency. While normal subjects displayed a left-lateralized fronto-temporo-parietal and bilateral cingulo-striatal-thalamic-cerebellar network, the activation pattern of stroke patients was determined both by the hypoperfused regions and infarcted areas of the brain. Specifically, patients showed diminished BOLD effect in the cortical regions that were hypoperfused, even though their infarcts were subcortical, and showed increased BOLD effect in the homologous regions of the normal hemisphere. This finding raises the possibility that cortical hypoperfusion in the absence of infarct can cause shift of language functions to the opposite, intact hemisphere. However, reduced BOLD effect in the task relative to rest was found in hypoperfused regions in two patients, raising the possibility that regional function persisted, even though vascular reactivity was impaired. Results illustrate the complexities of functional imaging studies of recovery in patients with vascular lesions.